مغربی استعمار یت کے افکار و نظریات : ایک تحقیقی جائزہ: Western Colonial Thought and Ideologies: An Analytical Study - Muhammad Zubair; Dr. Saima (International Research Journal of Arabic and Islamic Studies, 2024)
Western colonialism is rooted in a specific mindset shaped by metaphysical beliefs, values, and ideologies. Its cultural superiority stems from intellectual dominance rather than military might alone. Historical evidence suggests that lasting supremacy requires intellectual foundations, and the decline of any civilization begins with their erosion. Muslims' lack of deep understanding of Western colonial thought has led to three major issues: failure of sincere Islamic movements, uncritical acceptance and attempted Islamization of Western ideas, and misinterpretation of the Enlightenment as an extension of Islamic thought. These misunderstandings perpetuate Western intellectual dominance. This study emphasizes the need for a unified approach among Islamic movements to intellectually dismantle Western colonialism. It highlights the inseparability of ideologies like liberalism and communitarianism from their specific historical, political, social, and economic contexts, arguing that adopting these without context leads to distortion. By understanding these ideologies comprehensively, it is possible to resist intellectual colonization effectively and uphold authentic Islamic principles.